Traditional Processing of Moke Arak Based on Palm Sap in Wogowela Village, South Golewa District - Limbu, Nataniel Umbu; Bao, Antonia P.; Lea, Victoria C; Lede, Maria F.H.; Kelly, Mario J.; Leweng, Hendrikus A. (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Wogowela Village is one of the villages in Ngada Regency that has many home-based factories producing Moke Arak, where the production process is passed down from generation to generation from ancestors. The purpose of this study is to determine the process of making moke arak from palm sap water, which is done traditionally in Wogowela Village, South Golewa District, as well as the factors that influence its production process. The method used is descriptive exploratory with three data collection techniques: observation, interviews, and documentation. The process of making moke arak in Wogowela Village includes several stages: harvesting palm sap, collecting palm sap, distillation, and storage. Factors influencing the moke arak production process include high rainfall and the level of fire during distillation. High rainfall and unstable flames will reduce the quality of moke arak. The process of making moke arak in the village is done without fermentation. This differs from the process of making moke arak in some other villages in the regency. The results of this study serve as a scientific reference that not all moke arak in Ngada Regency are made thru the fermentation stage.